Training School Resource Officers to Improve School Climate and Student Safety Outcomes, Arizona, 2015-2017 - Summers, Jessica J. ([Verlag nicht ermittelbar], 2020)
This study is an experimental investigation of the effectiveness of integrating School Resource Officers (SROs) into multi-disciplinary teams in reducing risk behaviors in students, specifically the average number of disciplinary incidents over the course of three years (2015-2017). The authors focus on the following research questions: Do schools with SROs demonstrate significantly greater declines in student disciplinary incidents than schools with no SROs? Do schools with SROs who receive the enhanced training (intervention) show greater declines in student disciplinary incidents than schools whose SROs receive only the standard training? Do the answers to questions 1-2 vary by sub-populations in the schools such as students from racial/ethnic minority backgrounds, gender, and socioeconomic status?